Acculturation and sense of belonging: a study of young Pakistani students in Hong Kong. Issue 3 (3rd July 2022) - Karim, Shahid; Hue, Ming Tak
ABSTRACT: The question of a sense of belonging to a host society is paramount to the study of acculturation in the society of settlement. The study of acculturation seeks to examine how acculturating people make sense of belonging to both their country of origin and the receiving community, and the potential consequences of adaptation. Using Berry's acculturation typology as an analytical framework, this article examines the sense of belonging among a group of Pakistani secondary school students and compares their accounts of social identification with everyday sociocultural practices in Hong Kong. A phenomenographic analysis of the participants' interviews reveals a lack of congruence between their sense of belonging and their lived acculturative experience. The findings suggest that categorising acculturating people based merely on their sense of belonging offers a limited understanding of acculturation. The theoretical and research implications of the findings are also discussed.